Reverse Abdominoplasty Flap in Reconstruction of Post-Bilateral Mastectomies Anterior Chest Wall Defect - William HC Tiong; Normala Hj Basiron (Case Reports in Medicine)
Reverse abdominoplasty was originally described for epigastric lift. Since the work by Baroudi and Huger in the 1970s, it has become clear that reverse abdominoplasty application can be extended beyond just aesthetic procedure. Through the knowledge of anterior abdominal wall vascularity, its application had included reconstructive prospect in the coverage of various chest wall defects. To date, reverse abdominoplasty flap has been used to reconstruct unilateral anterior chest wall defect or for larger defect but only in combination with other reconstructive techniques. Here, we presented a case where it is used as a standalone flap to reconstruct bilateral anterior chest wall soft tissue defect post-bilateral mastectomies in oncological resection. In conclusion, reverse abdominoplasty flap provided us with a simple, faster, and satisfactory reconstructive outcome.